Sample stage designed for force modulation microscopy using a tip-mounted AFM scanner. Issue 5 (29th January 2016) - Lu, Lu; Xu, Song; Zhang, Donghui; Garno, Jayne C.
Abstract : Among the modes of scanning probe microscopy (SPM), force modulation microscopy (FMM) is often used to acquire mechanical properties of samples concurrent with topographic information. Abstract : Among the modes of scanning probe microscopy (SPM), force modulation microscopy (FMM) is often used to acquire mechanical properties of samples concurrent with topographic information. The FMM mode is useful for investigations with polymer and organic thin film samples. Qualitative evaluation of the mixed domains of co-polymers or composite films can often be accomplished with high resolution using FMM phase and amplitude images. We have designed and tested a sample stage for FMM constructed of machined polycarbonate. A generic design enables FMM experiments for instrument configurations with a tip-mounted SPM scanner. A piezoactuator within the sample stage was used to drive the sample to vibrate in the z -direction according to selected parameters. To evaluate the FMM sample stage, we tested samples of known composition with nanoscale dimensions for increasingly complex surface morphologies. Excellent resolution was achieved in ambient conditions using the home-constructed sample stage, as revealed for complex surfaces or multi-component samples. Test structures of nanoholes within a film of organosilanes provided the simplest platform with two distinct surface domains. Ring-shaped nanostructures prepared on Si(111) with mixed organosilanes provided three regions for evaluating FMM results. A complex sample consisting of a cyclic gel polymer containing fibril nanostructures was also tested with FMM measurements. Frequency spectra were acquired for sample domains, revealing distinct differences in local mechanical response. We demonstrate a practical approach to construct a sample stage accessory to facilitate z -sample modulation for FMM experiments with tip-mounted SPM scanners.